NON-RAYLEIGH OXYGEN ISOTOPE FRACTIONATION BY MINERAL EVAPORATION: THEORY AND EXPERIMENTS IN THE SYSTEM SIO2 - EXPERIMENTAL DATA IN THE SYSTEM MGO-SIO2-H2 TO 1.0 X 10-9 BAR AND 1870°C WITH VARIABLE OXYGEN FUGACITY - Young E.D.; Nagahara H.; Mysen B.O.; Audet D.M. (My University, 1998)
Experiments demonstrate that partial evaporation of solid silica at 1600-1700°C and low pressure (10-9 bar) results in enrichment of 18O/16O and 17O/16O in solid products. Evaporative residues formed in H2 or N2 gas at higher pressures (>10-5 bar) exhibit limited or negligible heavy isotope enrichment. The degree of enrichment is controlled by kinetic fractionation at the ablating grain surfaces, the rate of sublimation, and the efficacy of oxygen self diffusion in the solid. Observed isotopic effects are consistent with numerical simulations, confirming that vaporization of solid silicate and oxide minerals is a viable cause for non-Rayleigh fractionation of 16O, 17O, and 18O. Experiment and theory suggest that partial melting during evaporation is not required a priori to explain mass-dependent variations in oxygen isotope ratios in primitive meteoritical materials. Experimental determinations of the rates of ablation of appropriate minerals are required to evaluate the meteoritical data.